Spatial mapping of agricultural water productivity using SWAT model in upper Bhima catchment, India - Garg, Kaushal K.; Bharati, Luna; Gaur, Anju; George, B.; Acharya, Sreedhar; Jella, Kiran; Narasimhan, B. (Wiley, 2012)
The Upper Bhima River Basin is facing both episodic and chronic water shortages due to intensive irrigation development. The main objective of this study was to characterize the hydrologic processes of the Upper Bhima River Basin and assess crop water productivity using the distributed hydrologic model, SWAT. Rainfall within the basin varies from 450 to 5000?mm in a period of 3-4?months. The basin has an average rainfall of 711?mm (32 400?Mm3 (million cubic metres)) in a normal year, of which 12.8% (4150?Mm3) and 21% (6800?Mm3) are captured by the reservoirs and groundwater reserves, respectively, 7% (2260?Mm3) exported as runoff out of the basin and the rest (63%) used in evapotranspiration. Agricultural water productivity for sugarcane, sorghum and millet were estimated as 2.90, 0.51 and 0.30?kg m?3, respectively, which were significantly lower than the potential and global maximum in the basin and warrant further improvement. Various scenarios involving different cropping patterns were tested with the goal of increasing economic water productivity values in the Ujjani Irrigation Scheme. Analysis suggests that maximization of the area by provision of supplemental irrigation to rainfed areas as well as better on-farm water management practices can provide opportunities for improving water productivity.